STUDI ANALISIS KESADARAN HUKUM MASYARAKAT TENTANG KEPEMILIKAN AKTA PERKAWINAN DI DESA SUKASABA KECAMATAN MUNJUL - Reza Mahlevi; Wika Hardika Legiani; Febrian Alwan Bahrudin (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
ABSTRACT Marriage certificate is proof of marriage registration at the KUA, so that marriages can be recognized by the state and protected by law. But unfortunately, there are still people who do not have a marriage certificate. The purpose of this study was to determine and analyze the level of legal awareness as well as to analyze the factors that caused the community in Sukasaba Village, Munjul District not to have a Marriage Certificate. The research methodology used is descriptive qualitative, where data collection is carried out by direct interviews with informants / respondents. Research subjects (informants) are residents who do not have a marriage certificate validated by triangulation of sources by village officials and KUA Munjul sub-district. The results of this study are that there are 3 people who do not have a marriage certificate on the grounds of not knowing the existence of the Marriage Law and the obligation to register their marriage at the KUA, 3 people who do not have a marriage certificate for economic reasons, and there are 14 people who argue that it is not a problem even though they do not have a marriage certificate because old.